Fully Integrating Upper-Secondary Vocational and Academic Courses: A Flexible New Way? - Cain Polidano; Domenico Tabasso (Institute for the Study of Labor (IZA), 2016)
The tracking of students in upper-secondary school is often criticised for narrowing the career prospects of student in the vocational education and training (VET) track, which in many countries leads to the stigmatisation of VET courses. To tackle this problem, Australia blurred the lines between the two tracks by introducing VET courses that count to both a national VET qualification and university entry. In this study, we estimate the impacts of taking these courses on academic achievement and university entry using administrative data, propensity score matching and a decomposition method developed especially. We find that among those who intend to go to university, taking a VET course is associated with 5 percent lower academic achievement, due mainly to relatively weak achievement in VET, and an 8 percentage point lower chance of receiving a university offer. These findings tell a cautionary tale on the merits of integrating VET and academic courses.
Keywords: I20; I23; J24; 330; propensity score matching; university access; vocational education and training